Methodological aspects of design of didactic complex on engineering drawing - Goliiad, I (Professional Pedagogics, 2011)
The necessity for creating a didactic complex on engineering drawing for training of future skilled workers is under consideration. Structure, stages and advantage of didactic complexes creation is proposed.
Keywords: graphic preparation; didactic complex; engineering drawing; skilled worker